"Espelho de enganos, teatro de verdades" : um estudo sobre a mística que sustenta o Estado português e a defesa do governo pelo bem comum nos seiscentos - Simões, Tatiana Garcia de Oliveira (Universidade do Vale do Rio dos Sinos, 2010)
This thesis aims at discussing the dynamics of power relations that characterized the Portuguese monarchy in the context of the Restoration, which took place in 1640. Our purpose is to understand to what extent the bearings of public life and the power relations maintained between the King - the head of the Portuguese political body -, and his vassals - both inside and outside the kingdom - were in line with the theological and philosophical assumptions underpinning and legitimizing the Catholic political thought, whose intelligibility was guaranteed by the precepts of rhetoric that ordered the seventeenth century Portuguese political discourse. For this, we use three embossed political texts of political issues from that period of time. One of the texts is a letter written by Father Antonio Vieira to the Bishop of Japan, entitled Hope of Portugal, Fifth Empire of the World, first and second life of King D. João the Fourth, written by Gonçaliannes Bandarra, in 1659; the second is the History of the Future - Book Before the First, from the same author, in 1667, and the latter is the Art of Stealing, written by Father Manuel da Costa, in 1652.
Keywords: Estado português moderno; Cultura política Antônio Vieira; Manuel da Costa; Modern portuguese state; Political culture; Antônio Vieira; ACCNPQ::Ciências Humanas::História